Enabling reflexivity and the development of reflexive competence within course processes: a case study of an environmental education professional development course - Raven, Glenda C (Rhodes University, Faculty of Education, Department of Education, 2005)
This research was undertaken in the context of socio-economic transformation in South Africa, and more specifically, in the context of change in education policy. To support socio-economic transformation in South Africa after the first democratic elections in 1994, a competence-based National Qualifications Framework (NQF) was introduced in 1995. In responding to the particular socio-historical context of South Africa, the South African NQF is underpinned by the notion of applied competence, integrating practical, foundational and reflexive competence, which is the key and distinguishing feature of this competence-based framework. In this context of transformation, the research was aimed at an in-depth exploration of the notion of reflexivity and reflexive competence, and course processes that enable its development, with a view to providing curriculum development insights for learning programme development in the competence-based NQF, more broadly, and environmental education professional development programmes, more specifically. To enable these aims, the research was undertaken in the context of the Rhodes University / Gold Fields Participatory Course in Environmental Education (RU/GF course), as a case example of a professional development course that aims to develop critically reflexive practitioners. Within an interpretivist orientation, a multiple-embedded case study approach was used to gain insight into the relationship between course processes, reflexivity and the development of reflexive competence to clarify and provide a critical perspective on how competence develops in the context of the course. Data was collected over a period of one year using observation, interviewing and document analysis as the primary data collection techniques. Data was analysed through various phases and layers to inform data generation and the synthesising of data for further interpretation. Through the literature review undertaken within the study, various significant insights emerged around the notion of reflexivity and reflexive competence. Firstly, there appears to be a need to distinguish between reflexivity as social processes of change (social actions and interactions within social systems, structures and processes) and reflexive competence (a range of integrative elements of competence) that provides the evidence of an engagement within social processes of change. The second key insight emerging is the significance of social structure in shaping participation in reflexive processes, thus emphasising the duality of structure as both the medium for, and outcome of reflexive social actions and interactions and so challenges the deterministic conception of social structure. Further, the significance of an epistemologically framed notion of reflexivity and reflexive competence emerged, in the context of responding to the complex and uncertain quality of socio-ecological risks and in supporting change in context. Reflexivity, distinguished from processes of critical reflection, foregrounds a critical exploration of both knowledge and unawareness. As such a reinterpretation of reflexive competence is offered as a process of potential challenge to dominant and reigning forms of reasoning (knowledge frameworks) and consequent principles of ordering. Through this reframing of reflexive competence, the potential exists to destabilise dominant forms of reasoning and principles of ordering to create a broader scope of possibilities for action and change in context. This reframing of reflexive competence in the context of transformation in South Africa has critical implications for engaging within processes of learning programme design in the NQF to support an engagement within reflexive processes of change and the development of a range of integrative elements of reflexive competence. In this light, the study attempts to make the following contribution to curriculum deliberations within the context of environmental education and the NQF in relation to reflexivity, reflexive competence and change: ♦ Reflexivity is conceptualised as social processes of change with reflexive competence providing evidence of engagement within these social processes of change; ♦ An epistemologically framed conception of reflexivity and reflexive competence recognises how rules of reason and the ordering of the 'reasonable' person come to shape social life; and so ♦ Change is conceptualised as ruptures and breaks in dominant knowledge frames and the power relations embedded in these; ♦ Unawareness emerges as a key dimension within reflexive environmental education processes in responding to the unpredictable and uncertain nature of risks; ♦ An epistemological framing of reflexivity and reflexive competence highlights the need to develop open processes of learning to support the critical exploration of knowledge and unawareness; and ♦ Within this framing of reflexivity and reflexive competence, the difficulty emerges in specifically predefining reflexive competence to inform standard setting processes within a context of intended change. In framing data within this emerging conception of reflexivity and reflexive competence, a review of course processes highlighted potential areas for reorienting the RU/GF course to support change in context, for which I make specific recommendations. Drawing on the review of course processes in the RU/GF course, and in light of the reframing of reflexivity and reflexive competence, I further offer summative discussions as 'possible implications' for learning programme design in the South African competence-based NQF, broadly and environmental education professional development programmes in this framework, more specifically.
Keywords: Rhodes University / Gold Fields Course in Environmental Education; Environmental education -- Research -- South Africa; Environmental education -- South Africa -- Curricula; Competency-based education -- South Africa; Education and state -- South Africa; Education -- Research